Performance inflation in junior tennis: Longitudinal analysis and Bayesian forecasting of ranking thresholds, efficiency, and access equity - Bozdech, M. (PLOS ONE, 2026)
This study examined long-term trends, systemic dynamics, and predictive trajectories of junior male tennis performance within the International Tennis Federation (ITF) World Tennis Tour Juniors between 2004 and 2024. Using a longitudinal dataset of 8,082 ranked players, percentile-based performance thresholds (P90, P75, P50) were first derived from annual Total Ranking Points (TRP) distributions to represent the 90th-, 75th-, and 50th-percentile cut-offs in the ITF ranking system. These empirically determined thresholds were then used as reference criteria in binary logistic regression models to estimate corresponding performance boundaries for both TRP and Points per Event (PPE)—the latter serving as an efficiency-adjusted indicator derived from the ratio of TRP to the number of tournaments played. Exponential trend fitting and Bayesian time-series forecasting (Prophet) were subsequently applied to model long-term trajectories and project performance standards for the 2025-2029 period. Findings revealed a sustained and predominantly exponential increase in both TRP and PPE percentile thresholds, indicating that competitive attainment in junior male tennis has followed an accelerating trajectory. However, growth patterns differed in magnitude: TRP thresholds exhibited consistently steeper gradients than PPE thresholds across all percentile tiers, indicating that performance inflation appears to be more strongly associated with cumulative ranking-point expansion than with uniform increases in per-event scoring efficiency, although these indicators remain strongly correlated and should therefore be interpreted as complementary rather than independent mechanisms. Although efficiency-adjusted thresholds also demonstrated upward drift—particularly at the elite level (P90)—the magnitude of this growth remained comparatively moderate. Geographic analysis further identified a persistent concentration of elite players and tournaments within a limited group of nations, highlighting systemic inequities in access to ranking opportunities. Forecasts suggest that percentile cut-off thresholds will continue to rise over the next five years, reinforcing the need for adaptive performance strategies. For coaches, federations, parents, and other key stakeholders, sustainable athlete development will depend on balancing competition access and efficiency optimisation with adequate recovery, educational commitments, and psychosocial well-being. Collectively, these results position "performance inflation" in junior tennis as a multidimensional phenomenon shaped by structural accessibility, competitive efficiency, and temporal acceleration within the ITF ranking system.